Reformulation of Narcotics Regulations to Eliminate Inconsistent Interpretation for Narcotics Offenders - Anita Zulfiani; Hartiwiningsih; Dian Esti Pratiwi; Yussri Sawani (Pusat Strategi Kebijakan Hukum dan Peradilan Mahkamah Agung RI, 2026)
A considerable number of correctional facilities and detention centres in Indonesia are currently grappling with overcrowding issues, primarily driven by inmates involved in narcotics-related cases. This research aims to investigate the inconsistencies within narcotics regulations that lead to diverse interpretations of the law by law enforcement officials. The pressing aim of this study is to reduce the population of narcotics offenders serving prison sentences, thus alleviating the problem of overcrowding. This research adopts a qualitative methodology focusing on legislative and conceptual analysis. The research findings underscore the necessity for a revision of narcotics legislation. More specifically, this involves categorizing narcotics offenders based on their intent, making a clear distinction between